Beyond training mastering endurance, health, and life - Greenfield, Ben (Victory Belt Publishing, Inc., 2014)
Presents a guide to achieving peak fitness capability by optimizing performance, fat loss, and brain function, covering such aspects of health as nutrition, training, recovery, stress and time management, sleep, and digestion.